2020
DOI: 10.1155/2020/3631923
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Periodic Outbreak of Measles in Mainland China

Abstract: In mainland China, measles infection reached the lowest level in 2012 but resurged again after that with a seasonally fluctuating pattern. To investigate the phenomenon of periodic outbreak and identify the crucial parameters that play in the transmission dynamics of measles, we formulate a mathematical model incorporating periodic transmission rate and asymptomatic infection with waning immunity. We define the basic reproduction number as the threshold value to govern whether measles infection dies out or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…To show how well model (1) with periodic parameters matches seasonal fluctuation data, the simulation results are shown. Here, following [19,20,35,36], we assume that the transmission rate β(t) is a timeperiodic function with 12 months as a period, given by…”
Section: Case Study: Measles Outbreak In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…To show how well model (1) with periodic parameters matches seasonal fluctuation data, the simulation results are shown. Here, following [19,20,35,36], we assume that the transmission rate β(t) is a timeperiodic function with 12 months as a period, given by…”
Section: Case Study: Measles Outbreak In Pakistanmentioning
confidence: 99%
“…The parameters were estimated from demographic and epidemiological data, and numerical simulations showed the seasonal fluctuation of measles in China. Xue et al [19] used the model to investigate the periodic outbreak in mainland China; they recommended enhancing vaccination and implementing an optimal control system to minimize infections. The authors of [20] analyzed the seasonal spread of measles in China using a mathematical model that accounted for periodic transmission fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Memon et al (2020) reported that high vaccine coverage rate is vital for disease control [17]. Again, the study in [37] analyzed a dynamic model incorporating both periodic transmission and asymptomatic infection with waning immunity with the aim of identifying parameters that influence seasonal fluctuation of measles as well as provide optimal control measures to minimize the number of infected individuals and costs.…”
Section: Introductionmentioning
confidence: 99%
“…Althouse and Scarpino [2] explored the role of asymptomatic carriers in the resurgence of pertussis (whooping cough), highlighting that even if a high proportion of individuals are vaccinated, asymptomatic transmission can still sustain the disease in the population. Models have also been used to study the roles of asymptomatic transmission for other diseases, such as Zika infection [31], measles [32,46], respiratory syncytial virus (RSV) [35,42], etc.…”
mentioning
confidence: 99%